Menumbuhkan Jiwa Wirausaha Mahasiswa Peserta Pengenalan Kehidupan Kampus bagi Mahasiswa Baru (PKKMB) Sekolah Tinggi Ilmu Ekonomi Bima - Puji Muniarty; Nurhayati Nurhayati; Intisari Haryati; Jaenab Jaenab; Aliah Pratiwi; Nafisah Nurulrahmatiah (Jurnal Pengabdian Pada Masyarakat, 2021)
GENERATING ENTREPRENEURIAL SPIRIT FOR STUDENTS PARTICIPATING IN CAMPUS LIFE INTRODUCTION FOR NEW STUDENTS (PKKMB) OF SEKOLAH TINGGI ILMU EKONOMI BIMA. Higher education is a place to continue higher education, so adaptive, creative and innovative breakthroughs are needed to attract fresh gradations for the development of science to fulfill the study of prospective new students in the transition phase to become more mature and self-sufficient and accelerate the process of adapting students to the environment. new students and provisions for the success of studying at STIE Bima so that an Introduction to Campus Life for New Students (PKKMB) is needed with the aim of forming and realizing the character of superior, independent and responsible students. Therefore, tertiary institutions have an important role in producing quality graduates that can be used by stakeholders, the initial stimulus carried out by the Bima College of Economics (STIE) in producing complete human resources, namely by entrepreneurial exploration in PKKMB STIE Bima activities. fostering an entrepreneurial spirit for new students who do not yet have soft skills, knowledge and business skills. Participatory activity approach with the method of transferring knowledge from lecturers through the provision of PKKMB materials, observation and interviews with several informants during the entrepreneurship bazaar. The results showed that PKKMB participants were aware of business opportunities, were communicative and were confident when promoting their products during the bazaar.